Bede, Æthelberht, and the 'examples of the Romans' in early medieval England. - Rabin, Andrew (Early Medieval Europe, 2023)
In Book II, Chapter 5 of the Historia ecclesiastica, Bede writes that the Kentish king Æthelberht had, 'with the advice of his counsellors, established legal enactments according to the examples of the Romans.' This article argues that Bede's formulation serves as a means of characterizing the increasingly interventionist role played by early Kentish kings in making the laws issued in their names.